The quest for alpha : the holy grail of investing - Swedroe, Larry E. (Sweoe, Larry E. Bloomberg, 2011)
Final word on passive vs. active investingThe debate on active investing-stock picking and market timing-versus passive investing-markets are highly efficient and almost impossible to outperform-has raged for decades. Which side is right' In The Quest for Alpha: The Holy Grail of Investing, author Larry E. Swedroe puts an end to the debate, proving once and for all that active investing is likely to prove futile as the associated expenses-costs, fees, and time spent analyzing individual stocks and the overall market-are likely to exceed any benefits gained. The bookPresents research, data, and quotations that reveal it's extremely difficult to outperform the marketExplains why investors should focus on asset allocation, fund construction, costs, tax efficiency, and the building of a globally diversified portfolio that minimizes, if not eliminates, the taking of idiosyncratic, uncompensated risksOther titles by Swedroe: The Only Guide to Alternative Investments You'll Ever Need and The Only Guide You'll Ever Need for the Right Financial PlanInvestors are on a never-ending search for a money manager who will deliver returns above the appropriate risk-adjusted benchmark, aka the "Holy Grail of Investing." The Quest for Alpha demonstrates that it's a loser's game-while it's possible to win, it's so unlikely that you shouldn't try